Expanding the diagnostic lens: Whole exome sequencing in a neonate with arthrogryposis–renal dysfunction–cholestasis (ARC) syndrome - Gayathri Sreenivasan; Jane Hedrick; Anita Ware; Melanie Leong (Journal of Neonatal-Perinatal Medicine, 2026)
We report a term neonate who presented with early-onset conjugated hyperbilirubinemia, acholic stools, and imaging findings concerning for biliary atresia, including a contracted gallbladder and triangular cord sign on abdominal ultrasound. However, intraoperative cholangiography demonstrated normal bile flow. Persistently normal gamma-glutamyl transpeptidase (GGT), cholestasis, and renal tubular dysfunction prompted expanded evaluation. Whole-exome sequencing identified a pathogenic VPS33B variant, confirming Arthrogryposis–Renal dysfunction–Cholestasis (ARC) syndrome. Despite supportive management, his condition progressively declined, and he died at approximately 2 years of age following worsening cholestasis, reduced oral intake, and cardiorespiratory arrest at home. In this infant, the absence of arthrogryposis represented an incomplete and atypical phenotype at birth of an already rare condition. This case report and review of the literature expands the recognized clinical spectrum of ARC syndrome and underscores the importance of considering genetic etiologies in neonates with low-normal GGT cholestasis when conventional evaluation is inconclusive. Early integration of genomic testing may improve diagnostic accuracy, inform family counseling, and refine clinical decision-making in neonatal cholestasis.